Lexical comprehension within and across sign languages of Belgium, China and the Netherlands - Carl Börstell (Glossa, 2023)
There are hundreds of known sign languages around the world today, distinct languages each with its own historical and cultural context. Nevertheless, it is well known among signers who move through international spaces and across signing communities that a certain degree of mutual intelligibility is achievable during so-called cross-signing, even between historically unrelated sign languages. This has been explained by shared experiences, translanguaging competence and a higher degree of iconicity in the lexicons of sign languages. In this paper, I investigate one aspect of mutual intelligibility between four different sign languages: Sign Language of the Netherlands (NGT), Flemish Sign Language (VGT), French-Belgian Sign Language (LSFB) and Chinese Sign Language (CSL). Through a comprehension task with NGT signs, I analyze how accurately signers of the four sign languages identify NGT signs in an experimental sign-to-picture matching task, matching one target sign to one of four meaning choices: one target meaning and three distractors based on either form-similarity or plausible iconicity-mapping to the target sign. The results show that signers of VGT and LSFB perform better than CSL signers on this task, which may be attributed to lexical overlap, shared iconic mappings and experiences, as well as language contact due to geographic proximity. It is found that misidentification of target meanings is mostly caused by distractors with iconically plausible mappings between form and meaning. Across the four languages, signers’ self-evaluations of their performance on the lexical comprehension task correlate with test scores, demonstrating that they generally judge their level of comprehension accurately.